Role of non-coding RNA in exosomes for the diagnosis and treatment of osteosarcoma - Liu, Xin; Wang, Yaling; Wang, Chenwen; Wang, Xinyuan; Tang, Gangqiang; Xiong, Zhou; Zhou, Wei (Frontiers in Oncology, 2024)
Osteosarcoma (OS) is a malignancy characterized by the proliferation of osteoblasts that predominantly affects pediatric and adolescent populations. At present, early detection of OS is significantly lacking, coupled with treatment challenges such as high recurrence rates, increased side effects, and the development of drug resistance. Therefore, developing new diagnostic and therapeutic modalities is clinically significant. Exosomes are naturally occurring nanoparticles found in the body that contain various materials, including DNA, RNA, and proteins. Owing to their numerous beneficial properties, including histocompatibility and in vivo stability, they can be useful as drug carriers. With the development of competitive endogenous non-coding RNA (ncRNA) networks, the role of ncRNA in OS cell control has been increasingly studied. This review provides a thorough summary of multiple potential biogenetic pathways of different ncRNAs in exosomes, including microRNAs, long ncRNAs, and circular RNAs. Moreover, the review highlights their effects on OS cells and their potential applications in the diagnosis, treatment, and control of OS drug resistance. The interplay between different types of ncRNAs, which collectively affect OS through the networks of competing endogenous ncRNAs, is the primary focus of this research.